Respuesta :
Answer:
quadratic trinomial
Step-by-step explanation:
3x(x − 3) + (2x + 6)(-x − 3)
Distribute
3x^2 -9x + (2x + 6)(-x − 3)
FOIL
3x^2 -9x + -2x^2 -6x -6x -18
Combine like terms
x^2-21x-18
This has 3 terms so it is a trinomial
The highest power of x is 2 so it is quadratic
9514 1404 393
Answer:
- x² -21x -18
- quadratic trinomial
Step-by-step explanation:
Eliminating parentheses, we get ...
= (3x)(x) -(3x)(3) +(2x)(-x -3) +6(-x -3)
= 3x² -9x +(2x)(-x) +(2x)(-3) +(6)(-x) +(6)(-3)
= 3x² -9x -2x² -6x -6x -18
= x²(3 -2) +x(-9-6-6) -18
= x² -21x -18
The highest power is 2, so this is a quadratic.
There are 3 terms, so this is a trinomial.